The Impact of Covid-19 Pandemic on Breast and Thyroid Cancer Surgery: An Advantage or Disadvantage Factor? - Hermin Aminah Usman; Fauzan Ali Zainal Abidin; Akbar Maulana (Indonesian Journal of Cancer, 2021)
Background: Breast cancer (BC) and thyroid cancer (TC) are the types of cancer mostly treated at the Surgical Oncology Department with 24.1% and 6.8%, respectively, of all malignancies at Dr. Hasan Sadikin General Hospital. The delay in managing patients for both types of cancer will increase the risk of cancer stage progression. This study was conducted to determine the Covid-19 pandemic’s impact on delayed surgery due to longer waiting times in BC and TC patients.Methods: This research is a descriptive study. The data were collected from BC and TC patients who received surgery in the Surgical Oncology Department from April to June 2020 at Dr. Hasan Sadikin General Hospital. These data include the time of surgery, gender, age, stage of the disease, chemotherapy history, management, time from diagnosis until surgery, last time receiving neoadjuvant chemotherapy until surgery, and time of surgery on schedule.Results: Thirty-seven patients had undergone surgery; the stages of BC and TC patients were IIIB (66.6%) and II (50.0%), respectively. There were 31 BC patients (93.9%) who received neoadjuvant chemotherapy and underwent surgery, and total thyroidectomy with dissection was performed in 75% of TC patients. Operative procedures that were performed earlier than the schedule have been done in 20 (60.6%) and three patients (75.0%) for BC and TC patients, respectively, while 2 (0.6%) of BC patients were delayed in their management and no patient experienced a delay in management on TC.Conclusions: The management of BC and TC patients with various stages has received operation procedures faster than the previously determined schedule in the period from April to June 2020. These results also suggest a possible advantage for cancer patients requiring surgery, particularly patients with advanced BC who have received neoadjuvant chemotherapy. In certain conditions, it turns out that a pandemic may positively impact, especially in the management surgery of breast and thyroid cancer patients. However, limited time at the early start of the pandemic may change these conclusions.